SAFETY PERMIT EVALUATION IN CONFINED SPACE BASED ON INDONESIAN REGULATION - Nurvida, Nugrahani Marta; Widajati, Noeroel; Wahyudiono, Yustinus Denny Ardyanto; Imaduddin, Ahmad (HEARTY, 2025)
Working in confined spaces has high risks, such as inhaling hazardous substances, trapped, falling, falling objects, fires, and explosions. One work sector that uses a lot of confined spaces in its production process is the Steam Power Plant. In Indonesia, Paiton Steam Power Plant is one of the largest steam power plants, supplying electricity to the islands of Java and Bali. To reduce the risk of accident in confined spaces, the Indonesia government, through the Ministry of Manpower, has established the latest regulations on confined spaces, which must be implemented in all companies that use confined spaces. This research aims to evaluate the current procedure and regulation about confined spaces in one of the companies that operated Paiton Steam Power Plant with the latest regulations by the Indonesia Ministry of Manpower. By using descriptive qualitative with literature study instrument on documents, observations, and interviews with safety specialist and safety officers. The result is within 56 checklist point evaluation based on Indonesia Regulation, there are 7 points minor inconsistencies, and 1 point is major inconsistencies. The company has implemented the regulation really well and just need to do some adjustment in the future.